2010
DOI: 10.4103/0971-9261.70646
|View full text |Cite
|
Sign up to set email alerts
|

Beware of neonatal appendicitis

Abstract: We report a neonate with acute appendicitis who was mistakenly diagnosed and treated initially as neonatal necrotizing enterocolitis. The diagnostic dilemma of this rare and life-threatening condition in premature babies and newborns is underlined. Awareness of this rare condition and possible differential diagnosis in this age group is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 10 publications
3
45
0
1
Order By: Relevance
“…Although common in the pediatric population, appendicitis in newborns is rarely considered as a differential diagnosis in acute abdomen, and is an infrequent occurrence in children under two years of age, affecting only 2% of children in this age group (2) . It is pointed out that NA corresponds to only 0.04% -0.2% of cases in children under two years with less than 50 cases described in the last 30 years (3) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although common in the pediatric population, appendicitis in newborns is rarely considered as a differential diagnosis in acute abdomen, and is an infrequent occurrence in children under two years of age, affecting only 2% of children in this age group (2) . It is pointed out that NA corresponds to only 0.04% -0.2% of cases in children under two years with less than 50 cases described in the last 30 years (3) .…”
mentioning
confidence: 99%
“…The main factor that contributes to diagnostic delay is the low level of suspicion of NA in newborns, even with subtle clinical presentation already installed and which is erroneously treated as necrotizing enterocolitis (NEC) (2) . According to studies, the rarity of the inflammatory process in the vermiform appendix during the neonatal period is attributed to its still embryonic morphology, i.e.…”
mentioning
confidence: 99%
“…Recent trials have suggested that initial treatment with either peritoneal drainage or laparotomy may have equivalent results in stage IIIB NEC [23,24]. In contrast, non-operative management of NPA is usually not recommended [1]. The reported failure rate for non-operative management of perforated appendicitis in children ranges from 10% to 40% [25][26][27].…”
Section: Managementmentioning
confidence: 99%
“…The reported failure rate for non-operative management of perforated appendicitis in children ranges from 10% to 40% [25][26][27]. In light of increasing non-operative management of NEC, a missed diagnosis of perforated appendicitis may explain failure of drain placement in a subset of patients [1]. Patients who fail conservative management may be at higher risk for postoperative complications and extensive bowel resection [25,28,29].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation